Hippocampal neuron firing and local field potentials in the in vitro 4-aminopyridine epilepsy model - Gonzalez-Sulser, Alfredo (American Physiological Society, 2012)
Excessive synchronous neuronal activity is a defining feature of epileptic activity. We previously characterized the properties of distinct glutamatergic and GABAergic transmission-dependent synchronous epileptiform discharges in mouse hippocampal slices using the 4-aminopyridine model of epilepsy. In the present study, we sought to identify the specific hippocampal neuronal populations that initiate and underlie these local field potentials (LFPs). A perforated multielectrode array was used to simultaneously record multiunit action potential firing and LFPs during spontaneous epileptiform activity. LFPs had distinct components based on the initiation site, extent of propagation, and pharmacological sensitivity. Individual units, located in different hippocampal subregions, fired action potentials during these LFPs. A specific neuron subgroup generated sustained action potential firing throughout the various components of the LFPs. The activity of this subgroup preceded the LFPs observed in the presence of antagonists of ionotropic glutamatergic synaptic transmission. In the absence of ionotropic glutamatergic and GABAergic transmission, LFPs disappeared, but units with shorter spike duration and high basal firing rates were still active. These spontaneously active units had an increased level of activity during LFPs and consistently preceded all LFPs recorded before blockade of synaptic transmission. Our findings reveal that neuronal subpopulations with interneuron properties are likely responsible for initiating synchronous activity in an in vitro model of epileptiform discharges.